Exploring smokers' perspectives on health status and health seeking behavior: a qualitative exploration - Ismail, Muhamad Al-Muizz; Mohamad Shariff, Nurasikin; Nurumal, Mohd Said; Abdul Rahman, Razlina; Mohd Mokhtar, Hanida Hani (Prince of Songkla University, 2025)
Objective: Smokers might tend to ignore when communicating about smoking health risks. We used Bourdieu’s conceptual tool to guide and explore their perception of being healthy despite their smoking behavior and their health seeking practice. Material and Methods: A qualitative method, using a semi-structured interview as the main method of collecting the data, was used. This method was implemented because of its flexibility in the exploration, based on participant responses. Results: The findings are reported as per the thematic analysis of 15 purposively selected participants. The ages of the 15 participants varied from 20 to 55 years old, and they were selected from the quantitative study to participate voluntarily in this qualitative exploration. Among them, 14 were males and one was female. The ethnic representation in this qualitative part were Malays (n=14) and Chinese (n=1). The duration of smoking varied in the sample, with the majority smoking for more than five years. Conclusion: This study better understands smokers’ health perception and their health-seeking behavior. Firstly, the perception of the less harmful effects of smoking on the health of smokers was understood within the views of Bourdieu’s Theory of Cultural Health Capital, which, in turn poses challenges to smoking cessation programs and campaigns. This study reported that smokers perceived themselves as healthy, and thus continued their smoking habit despite knowing its side effects.